Prevalence and risk factors for high-risk human papillomavirus infection among women from three southern geopolitical zones of Nigeria - Onwuamah, Chika Kingsley; Feng, Ning; Momoh, Abidemi Esther; Uwandu, Mabel; Ahmed, Rahaman Ademolu; Idigbe, Ifeoma; Vincent, Grace Deborah; Ogbu, Chinenye Angela; Okonkwo, Nkem; Sokei, Judith; Abimbola, Bowofoluwa Sharon; Ojopagogo, Temiloluwa; et al. (Frontiers in Oncology, 2023)
Introduction : Human Papillomavirus (HPV) infection is a risk factor for cervical cancer, the fourth most common cancer among women globally. Its burden is the highest in sub-Saharan Africa, with over 90% mortality. Interventions may fail without evidence-based data on stratified prevalence and risk factors among most at-risk women across Nigeria.Methods: A cross-sectional comparative study, with participants recruited from the Nigerian Institute of Medical Research's Clinics, NGO outreaches, a cancer screening centre and a university teaching hospital. Questionnaires were self-administered. Trained medics performed sampling at healthcare facilities, and self-sampling was used at outreaches.Results: Nine hundred eighty-five study participants were recruited. About 37% and 27% of the women knew about HPV and its vaccines, respectively, but only 6% confirmed vaccination with HPV vaccines. HPV prevalence was highest among women with unknown marital status (35.9%), single women (33.8%), widowed/divorced/separated women (30.3%), and married/cohabiting women (19.6%). HPV infection was significantly higher among women who take alcohol (odds=1.7 [95% CI: 1.2-2.4]) and women who smoke (odds=2.6 [95% CI: 1.4 -4.6]. HPV strains detected included HPV16 (1.3%), HPV18 (1.5%), Low Risk (0.2%) and Other High-Risk groups (19.7%).improving awareness and prevention would be impactful. Such interventions could also target HIV-positive women, women presenting with sexually-transmitted infections, who smoke and frequently drink alcohol.